Panbiogeography : tracking the history of life - Craw, R. C. (Robin C.) (Oxford biogeography series, 1999)
"The authors show how geographical patterns of animal and plant distribution contribute directly to understanding and interpreting evolutionary history. They also make a case for reinstating geography as a critical element in evolutionary biology. An innovative exploration of the roles of geology, ecology, and evolution in biogeography, this book includes new methods, modes of classification, and ways of measuring biodiversity."--Jacket